Análisis de la adquisición de ‘Tema-Rema’ en producciones escritas por estudiantes universitarios de Gramática inglesa - Maussion de Candé, Ana María (2022)
The current thesis analyzes the use of the ‘theme-rheme’ construct in the written productions of twenty-nine third year students at Facultad de Lenguas, Universidad Nacional de Córdoba. The study stems from the reading and writing difficulties detected in students at University level, which have a direct impact on their writing ability. The construct of ‘theme-rheme’, as viewed from Systemic Functional Theory, is central in this study, since it serves as the analytic tool as well as a device for the instruction of textual organization in the students’ written productions. The instruction on ‘themerheme’ is also guided by Genre Pedagogy. The study aims at analyzing the effects the ‘theme-rheme’ construct has in the improvement of students’ textual productions.